A new highly troglomorphic Loxosceles (Araneae: Sicariidae) from Brazil - Souza, Maysa F.v.r.; Ferreira, Rodrigo L. (Zootaxa, 2018)
The spiders of the genus Loxosceles have been reported from caves in several regions of the world. Despite their commonness in subterranean habitats, the occurrence of troglomorphic species is quite rare. A new cave-dwelling species found in the Brazilian Caatinga can be included in the restricted list of troglomorphic Loxosceles by presenting the following troglomorphic traits: eyes with reduced diameter, absence of pigment around the eyes, appendage elongation and pale coloration. Thus, the aim of this study is to describe a new highly troglomorphic species of Loxosceles from Brazil, corresponding to the first troglomorphic species from South America. Loxosceles troglobia sp. nov. belongs to the gaucho group and can be distinguished from the other species of this group mainly by the presence of the troglomorphic characteristics mentioned above and by the shape of the female spermathecae and the male palp. The morphological traits, together with the fact that the new species was found only in inner and very humid portions of two nearby caves, indicate that it is troglobitic.